Production techniques of photoplay magazines: the example of atọ́ka, a yorùbá photodrama (2019)
The Yorùbá theatre practitioners employed the print media – tagged photoplay magazine – as production medium for several of its plays during the second half of the twentieth century. The first and foremost publication in the photoplay genre was named Ató ḳ a. A unique outlet of dramatic expression by the Yorùbá theatre companies from 1967 – 1991. However, Atóka has received little attention from researchers. The theory of Total Quality Management (TQM) was employed for the study. The objective of this study is to document Atóka’s production techniques and put its contributions to the development of Yorùbá entertainment industry on record. The primary data consisted of 108 editions (25%) randomly selected from a total of 430 editions published. In-depth interviews were conducted with all the five editors and one former photographer of Atóka. Findings showed that Atóka was a fusion of dramatic arts, photographic arts and publishing arts. Its complex and sophisticated production was also a melting pot of different specialisations and disciplines. Atóka had an electrifying impact on its teeming readers across Nigeria and beyond. This paper is broadly discussed under: introduction, concept of TQM, origination and design, editorial and editing, printing, discussion of findings, and conclusion.